Methodology for Low-Field, Portable Magnetic Resonance Neuroimaging at the Bedside - Prabhat, Anjali M.; Crawford, Anna L.; Mazurek, Mercy H.; Yuen, Matthew M.; Chavva, Isha R.; Ward, Adrienne; Hofmann, William V.; Timario, Nona; Qualls, Stephanie R.; Helland, Juliana; Wira, Charles; Sze, Gordon; et al. (Frontiers in Neurology, 2021)
Neuroimaging is a critical component of triage and treatment for patients who present with neuropathology. Magnetic resonance imaging and non-contrast computed tomography are the gold standard for diagnosis and prognostication of patients with acute brain injuries. However, these modalities require intra-hospital transport to strict, access-controlled environments, which puts critically ill patients at risk for complications and secondary injuries. A novel, portable MRI (pMRI) device that can be deployed at the patient’s bedside provides a needed solution. In a dual-center investigation, Yale New Haven Hospital has obtained regular neuroimaging on patients using the pMRI as part of routine clinical care in the Emergency Department and Intensive Care Units since August of 2020. Massachusetts General Hospital has begun using pMRI in the Neuroscience Intensive Care Unit since January 2021. This technology has expanded the population of patients who can receive MRI imaging by increasing accessibility and timeliness for scan completion by eliminating the need for transport and increasing the potential for serial monitoring. Here we describe our methods for screening, coordinating, and executing pMRI exams and provide further detail on how to scan specific patient populations.